(3GdLhgQ GdfVjO aj TQM GdJLQjOs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3OGQ GdSdWfI (B- (3WgQGfs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3GdebUO GdKGfj aj GdLhGgQ hGdCYQGV hajg aUhd , GdChd aj GdLhGgQ bOe eHGMKgG Ydi eHGMK GdCYQGV dCf hLhO GdYQV eJhba Ydi hLhO GdLhgQ afGH Cf jbOe HjGf GdCMhGd (B...s
(3BNQgG (B:s
.. (3daX Cf jfaYd hCf jaYd Ydi GdGfaYGd hGdaYd dCfgeG bO jbGdGf ddMGUd HYO GfbWGY GdMQcI hCfgG GdebhdI eG cGf JhLgG Edi ZGjI aj hVY Ch cja Ch ZjQ Pdc ZjQ eSJbQ ef MjK gh cPdc hdaX Gf jfaYd hCf jaYd eNUhU HPdc (B.s
(3JHUQI GdYfhGf (B:s
(3aj TQM efWb GdJLQjOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/227s
(3GdPQjYI (B5- 206 ( 1356 )s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds